Technical Analysis of Grid Connected 1 kWP Rooftop Solar PV for Residential Consumer at Urban Areas of Lalitpur, Nepal - Gautam, Rupesh; Darlami, Hari Bahadur (Journal of Science and Engineering, 2021)
Integration of rooftop solar PV by a residential consumer to the grid is beneficial to both consumer and grid if integrated optimally. The minimization of power loss by improving the voltage profile on the grid side and reducing the electricity bill by improving energy deficiency faced by the residential consumer is the benefit of the integrated PV system. The preparation of this paper is based on the study of grid impact analysis and performance analysis of solar among the urban areas of Lalitpur. First, the grid impact and optimum size calculation are performed in IEEE-33 and IEEE-15 bus test system, and Pulchowk feeder is taken for the study of real scenario. Improvement of voltage profile, loss reduction, and the number of houses feasible for injecting PV generation has been demonstrated graphically. The power loss is found to be reduced by 62.5% after injecting solar PV into the grid. PVsyst has been used for the performance analysis of the PV array and the performance ratios are within limits with a capacity factor of 0.177 and performance ratio of 0.74 and system yield factor of 4.24 kWh/kWp/day. From all the results and performance analysis, it can be concluded that integration of 1 kWp rooftop solar is technically feasible if the optimum number of houses are allowed to inject PV array power at the optimum location.